Путешествие из Петербурга в Москву - Радищев Александр Николаевич (Азбука-классика, 2017)
Экземпляры: ф7 (20230210) / Инвентарный номер: 64297 / Цена: 96.00 / Сис.шифр: Р1 / Авт.знак: Р 15 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)1